ChemInform Abstract: An Expedient Route to Highly Diversified [1, 2, 3]Triazolo[1, 5‐a][1, 4]benzodiazepines and Their Evaluation for Antimicrobial, Antiproliferative and in silico Studies. Issue 52 (10th December 2015) - Sudhapriya, N.; Nandakumar, A.; Arun, Y.; Perumal, P. T.; Balachandran, C.; Emi, Nobuhiko
Abstract: Some title benzodiazepine derivatives are found to exhibit a broad spectrum of antibacterial activity and potency with respect to standard drugs streptomycin and ciprofloxacin.